Komparasi Karakteristik Visual dan Elemen Fisik Bangunan Budaya di Kota Pontianak : (Studi Kasus : Keraton Kadariah dan Rumah Radakng) - Andra Almeina; Hartanto Budiyuwono (Pusat Riset dan Inovasi Nasional, 2025)
Architecture is the realization of cultural values, history, and wisdom of the local community reflected in the physical form of buildings. This research aims to examine and compare the visual character of the physical elements of two cultural buildings in Pontianak City. These two buildings represent two majority groups, namely Malay and Dayak cultures, which have distinctive visual characters and physical architectural elements. The research used case study method, field observation, visual documentation, and identification of the physical elements. The results showed that physical elements can be seen with symbolic shapes, materials, colors, and ornaments. The visual character of the Kadariah Palace is identical to the shape of the linmas roof and multi-storey saddle, dominated by golden yellow, as well as floral carvings and repetitive geometric patterns full of symbolic meaning, and historical physical elements are also found as supporting attributes of the area. While Rumah Radakng found several elements in the form of massive stage structures, repetitive columns, predominantly red colors and natural colors of wood, as well as typical Dayak geometric ornaments that have spiritual symbolic meaning. Although different in visual and symbolic expression, both are important representations of Pontianak City's local architectural identity that is deeply rooted in their respective cultures. These findings are expected to serve as a foundation for readers who need different visual characters and appropriate physical elements to represent Pontianak City in the development of a cultural building.